INTEGRASI PENDIDIKAN ISLAM DENGAN SIKAP SPRITUAL PADA MATERI AKHLAK KELAS VIII SMP - Rina Nofriana; Fadriati Fadriati (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2022)
This article examines the integration of Islamic education with spiritual attitudes in morals. The problem is how to integrate Islamic education with spiritual attitudes in morals? The purpose of this study is to determine the integration of Islamic education with spiritual attitudes in the material of morality. The research was conducted with a qualitative approach with library research methods (Library Research). Data were collected by examining various literatures related to Islamic Education with Spiritual Attitudes. The data findings were then analyzed and presented descriptively in the form of a narrative. The results of the study found that the integration of Islamic education with spiritual attitudes in moral material can be done by the way teachers are expected to integrate Islamic education with spiritual attitudes into learning objectives, learning steps, and assessment of learning outcomes. Having high authority in designing, implementing and evaluating learning.